Multiscale Mechanobiology of Bone Remodeling and Adaptation - Pivonka, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book presents state-of-the-art developments in multiscale modeling and latest experimental data on multiscale mechanobiology of bone remodeling and adaptation including fracture healing applications. The multiscale models include musculoskeletal models describing bone-muscle interactions during daily activities such as walking or running, micromechanical models for estimation of bone mechanical properties, bone remodeling and adaptation models, cellular models describing the complex bone-cell interactions taking into account biochemical and biomechanical regulatory factors. Also subcellular processes are covered including arrangement of actin filaments due to mechanical loading and change of receptor configurations.
Bone cell biology and mechanobiology -- Disease systems analysis of osteoporosis and treatments -- Bone quality assessment across the scales -- Interaction of bone tissue with other tissues including muscle, cartilage, and vascularization -- Musculoskeletal modeling of human movement -- Image-based 3D micro-FE modeling.
Keywords: Mechanics, Applied; Solids; Biomaterials; Orthopedics; Solid Mechanics; Biomaterials; Orthopaedics